Riddles of Andalusian grammar to the grammarians - OBAID, MUDHER SAHIB; KADHIM , HAYDER KAREEM (International Journal of Psychosocial Rehabilitation, 2020)
This research dealt with an important aspect of the Arab heritage, which is the role of the Andalusian school in Arabic grammar. It showed some of what the Andalusia’s added to the Arabic linguistic lesson, especially what emerged from their comments and inquiries on the views of the school and Kufic pioneers of the school, which contributed to the manifestation of some of the problems that the visions stood And Kufic. The research required mentioning some of the examples of Al-Andalus grammarians, and it was based on three models of those challenges that show the contribution of Andalusians and their role in the Arab grammar lesson, then mentioned some Andalusian names that had the most prominent role in the Andalusian school. The first model showed the role of Ibn Malik to resolve the dispute contained by the scholars of visual and Kufic grammar in the entry of the thousand and the lam over the sentence, where the opinion of Ibn Malik on his permissibility and popularity in Arabic grammar. As for the second model, it dealt with the controversial issue of preventing dismissal of the disbursed, as a dispute arose between it being banned by the Basraians and its specialization in poetry for the Kofi’s, but Al-Suhaili, one of the pioneers of the Andalusian school, said that it is permissible with poetry and other than poetry and stipulating it with flags. The third model dealt with the issue of disagreement regarding the permissibility of removing the pronoun referring to the beginner, as that was permitted by the visions and prohibited by Al-Shanmari; Because the pronoun represents the connection within the sentence and its deletion deludes separation.